Evaluating the Potential of Plukenetia volubilis Linneo (Sacha Inchi) in Alleviating Cardiovascular Disease Risk Factors: A Mini Review - Izzat Zulhilmi Abd Rahman; Nur Syahidah Nor Hisam; Amilia Aminuddin; Adila A. Hamid; Jaya Kumar; Azizah Ugusman (MDPI AG, 2023)
Plukenetia volubilis Linneo or Sacha Inchi (SI), a traditional natural remedy indigenous to Peru and Brazil, has garnered global attention due to its exceptional nutritional composition. Its protective effects against various non-communicable diseases, notably cardiovascular disease (CVD), have become a subject of interest in recent research. This comprehensive review summarizes the existing evidence from 15 relevant articles concerning the impact of SI on common CVD risk factors, including dyslipidemia, obesity, diabetes, and hypertension. The relevant articles were derived from comprehensive searches on PubMed, Scopus, Google Scholar, and Web of Science using predefined criteria and keywords related to the topic. Overall, SI demonstrated positive effects in attenuating dyslipidemia, obesity, diabetes, and hypertension. The multifaceted mechanisms responsible for the protective effects of SI against these CVD risk factors are primarily attributed to its antioxidative and anti-inflammatory properties. While preclinical studies dominate the current scientific literature on SI, there are limited clinical trials to corroborate these findings. Therefore, future well-designed, large-scale randomized clinical trials are highly recommended to establish the efficacy of SI and determine its optimal dosage, potential drug and food interactions, and practical integration into preventive strategies and dietary interventions for the high-risk populations.